Aspect du Groenland - Allard, Hector (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1964)
The settlement of Greenland, the world's largest island, dates back at least 4,000 years but the present population numbers no more than 35,000 and is very unevenly distributed throughout the area — 40 per cent of the inhabitants are grouped along the island's south-west coast. However, major increases in the population in recent years have brought about serious housing and land communications problems and a pressing need for improved community facilities. Greenland's economy is based upon the exploitation of natural resources, mainly game, fish and minerals. With the exception of a few meat and fish processing plants established in recent years secondary industry is almost non-existent. Increased investment and improvement of the educational System appear to be keystones to the future development of this isolated land.